2018
DOI: 10.1103/physrevb.97.075137
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase transitions from Harper to Fibonacci crystals

Abstract: Topological properties of Harper and generalized Fibonacci chains are studied in crystalline cases, i.e., for rational values of the modulation frequency. The Harper and Fibonacci crystals at fixed frequency are connected by an interpolating one-parameter Hamiltonian. As the parameter is varied, one observes topological phase transitions, i.e., changes in the Chern integers of two bands due to the degeneracy of these bands at some parameter value. For small frequency, corresponding to a semiclassical regime, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
(133 reference statements)
1
16
0
Order By: Relevance
“…The very low value of the optical scattering rate together with the plasma frequency determined above allows us to estimate the resistivity to be ρ DC (T = 10K) ≈ 0.5± 0.2 µΩ · cm, very close to what is reported in recent transport experiments [9,14]. Combined with our observation of a frequency independent scattering rate up to the vHS energy scale E vHS suggests therefore that at low temperature the transport experiments are dominated by simple impurity and electron-electron scattering.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The very low value of the optical scattering rate together with the plasma frequency determined above allows us to estimate the resistivity to be ρ DC (T = 10K) ≈ 0.5± 0.2 µΩ · cm, very close to what is reported in recent transport experiments [9,14]. Combined with our observation of a frequency independent scattering rate up to the vHS energy scale E vHS suggests therefore that at low temperature the transport experiments are dominated by simple impurity and electron-electron scattering.…”
Section: Resultssupporting
confidence: 86%
“…One such example is PdTe 2 , which features both bulk Dirac points [1][2][3] as well as topological surface states [4] in combination with a transition to a superconducting phase with T c = 1.4 -2 K [5][6][7][8]. The superconducting state is conventional with an isotropic superconducting gap [8][9][10][11]. One peculiarity observed in these experiments is that PdTe 2 supports a type-I superconducting state [8,12], but recently some surface effects have been observed that leave open the possibility for an interesting surface superconducting state [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The candidate type II Dirac semimetal PdTe 2 [1][2][3] superconducts below 1.7 K [4][5][6][7][8]. Though initial experimental papers suggested the possibility of an unconventional nature of the superconducting phase of PdTe 2 , a number of experiments confirmed that the superconductivity in PdTe 2 is conventional in nature [9,10]. However, some of these experiments found evidence of type I behaviour as far as the magnetic properties of the superconducting phase of PdTe 2 are concerned [4,11,12].…”
mentioning
confidence: 99%
“…Now, the quantum Hamiltonian (30) is the Harper one [29], whose energy bands have Chern numbers uniquely determined by the TKNN Eq. (25). Specifically, in the case of s = 1/p with p odd, one has ′ s = 2 s = q ′ /p ′ with q ′ = 2 and p ′ = p. Using Eq.…”
Section: Case Of η =mentioning
confidence: 99%
“…We start from the Diophantine equation (25) for the total Chern number σ(b) of the lowest b bands and divide this equation by p. We then take the limit of q, p → ∞ of irrational s , choosing the lowest b bands (b → ∞) to be those below some fixed gap. Denoting b/p in this limit by ζ, 0 < ζ < 1, we obtain…”
Section: (A) and 5(b)mentioning
confidence: 99%